Electrical engineering equipment for generating and measuring of complete pulse current of artificial lightning in the conditions of high-voltage electrophysics laboratory - Baranov, M. I.; Buriakovskyi, S. G. (Національний технічний університет "Харківський політехнічний інститут", 2024)
Goal. Decision of problem scientific and technical task on the reliable generating and measuring in the conditions of high-voltage electrophysics laboratory basic component of complete pulse current of artificial lightning with the rationed amplitude-temporal parameters (ATPs) with the use of the modernized generator of current of lightning of type of UITOM-1. Methodology. Bases of the applied electrical engineering, electrodynamics and electrophysics, electrophysics bases of technique of high-voltage and high pulse currents, bases of high-voltage pulse technique and measuring technique. Results. Information, which specify on a decision at Research and Design Institute "Molniya" of National Technical University "Kharkiv Polytechnic Institute" problem scientific and technical task, related to the reliable generating and measuring in the conditions of high-voltage electrophysics laboratory of complete pulse current of artificial lightning, which contains pulse A- (repeated pulse D-), intermediate B- and long-term C- (shortened long C*-) components of this current, is resulted, ATPs which answer the hard technical requirements of normative documents of the USA of SAE ARP 5412: 2013, SAE ARP 5414: 2013 and SAE ARP 5416: 2013. Short information is indicated about the applied electrical circuits of separate high-voltage generators of pulse currents of condenser type of GIC-A (GIC-D), GICB and GIC-C (GIC-C*), which it is worked as synchronous appearance on the general electrical loading in composition the modernized powerful high voltage generator of complete pulse e current of artificial lightning of type of UITOM-1, and in-use highvoltage measuring facilities which contain the heavy-current low-resistance shunts of type of SHK-300 for simultaneous registration with their help on examinee on stability to lightning devices objects of aviation and space-rocket technique of ATPs proper component of complete i pulse current of artificial lightning. Technical examples are resulted and the row of results of practical application of the indicated domestic powerful high-voltage proof-of-concept electrophysics equipment is described at the tests of elements of some aircrafts (ACs) on resistibility to the direct action on them of complete pulse current of artificial lightning with rationed ATPs. Originality. A problem is formulated and having the important applied value in area of aviation and space-rocket technique for the leading countries of the world scientific and technical task on the reliable generating and measuring in the conditions of high-voltage electrophysics laboratory indicated component of complete pulse current of artificial lightning with rationed ATPs and concrete electro-technological ways and hardware are indicated for its successful decision. Practical value. The use of the modernized powerful high-voltage generator of complete pulse current of artificial lightning of type of UITOM-1 developed in practice and created in Ukraine will allow to conduct the real verification on resistibility to the action of lightning of different side systems, devices and construction elements, containing metallic and composition materials, both again developed and modernized ACs, that will be instrumental in the increase of vitality of such ACs in the extreme terms of their flight and stay in an electrical active earthly atmosphere with flowing in it storm electrical discharges.

Приведені дані, які вказують на вирішення в НДПКІ "Молнія" НТУ "ХПІ" проблемної науково-технічної задачі, пов'язаної з надійним генеруванням і вимірюванням в умовах високовольтної електрофізичної лабораторії повного імпульсного струму штучної блискавки, що містить імпульсну А- (повторну імпульсну D-), проміжну В- і тривалу С- (укорочену тривалу С*-) компоненти даного струму, які відповідають технічним вимогам нормативних документів США SAE ARP 5412: 2013, SAE ARP 5414: 2013 і SAE ARP 5416: 2013. Вказані відомості про застосовані електричні схеми окремих високовольтних генераторів імпульсних струмів конденсаторного типу ГІС-А (ГІС-D), ГІС-В і ГІС-С (ГІС-С*), що синхронно працюють на загальне електричне навантаження у складі модернізованого потужного високовольтного генератора струму штучної блискавки типу УИТОМ-1, і використовувані високовольтні вимірювальні засоби, які містять удосконалені низькоомні шунти типу ШК-300 для одночасній реєстрації за їх допомогою на випробовуваних на блискавкостійкість пристроях об’єктів авіаційної і ракетно-космічної техніки амплітудно-часових параметрів (АЧП) відповідних компонент повного імпульсного струму штучної блискавки. Приведені технічні приклади і описані деякі результати практичного застосування вказаного модернізованого вітчизняного високовольтного електрофізичного обладнання при випробуваннях елементів вітчизняних літальних апаратів на стійкість до прямої дії на них основних компонент імпульсного струму штучної блискавки з нормованими АЧП.
Електротехнічне обладнання для генерування і вимірювання повного імпульсного струму штучної блискавки в умовах високовольтної електрофізичної лабораторії
Keywords: pulse current of artificial lightning; modernized high-voltage generator of current of lightning; shunt; generating; measuring; components of current of lightning; імпульсний струм штучної блискавки; модернізований високовольтний генератор струму блискавки; шунт; генерування; вимірювання; компоненти струму блискавки